Pitavastatin reduces intestinal fibrosis in chronic colitis and inhibits colon fibroblast activation by enhancing MMP-9 expression via the IGF-1/IGF-1R pathway - Mengran Zhang; Hongping Lu; Jun Cheng (Brazilian Journal of Medical and Biological Research)
Statins have been shown to have antifibrotic effects on various tissues and organs, but their ability to improve chronic colitis-associated intestinal fibrosis and their mechanisms of action remain unclear. The objective of this study was to investigate the role of pitavastatin in chronic colitis-associated intestinal fibrosis and its possible mechanisms. We established a mouse model of chronic colitis-associated intestinal fibrosis through repeated administration of dextran sodium sulfate (DSS) and treated the mice with pitavastatin. The severity of intestinal fibrosis, serum inflammatory factor levels, and expression levels of intestinal fibrosis-related genes in mice were assessed using pathological histological staining, immunohistochemical staining, reverse-transcription PCR, RNA sequencing, and enzyme-linked immunosorbent assay. In vitro, we treated a human colon fibroblast cell line (CCD-18Co) with or without transforming growth factor-β1 stimulation using pitavastatin. Western blot, Cell Counting Kit-8 assay, and Transwell assay were used to analyze the activation of colonic fibroblasts, protein expression levels of genes related to intestinal fibrosis, and cell proliferation and migration abilities. Pitavastatin significantly attenuated DSS-induced chronic colitis and intestinal fibrosis. In vitro, pitavastatin concentration-dependently inhibited the activation of CCD-18Co cells, significantly reduced the expression levels of the intestinal fibrosis-related proteins Col1A1, IGF-1, IGF-1R, MMP-3, and TIMP-1, and significantly inhibited cell proliferation and migration while markedly increasing MMP-9 protein expression. Additionally, after silencing the IGF-1 and IGF-1R genes in CCD-18Co cells, the promotion of MMP-9 expression by pitavastatin was significantly inhibited. These findings suggest that pitavastatin may be a promising antifibrotic drug for future treatment of intestinal fibrosis.